Risk and responsibility - Leiss, William, 1939- (CEL - Canadian Publishers Collection., 1994)
William Leiss and Christina Chociolko explain that controversies arise in part because many participants try to avoid assuming full responsibility for the consequences of the risk-taking they advocate. For example, one can indulge in the pleasure of nicotine addiction despite an awareness of the health risks and count on a publicly funded health care system to assume the responsibility for dealing with the resulting illnesses. They provide detailed case studies of the controversies over the effects of exposure to power frequency electric and magnetic fields and to the chemical pesticides alar and antisapstains. Shorter studies of exposure to tobacco, formaldehyde, and the pesticide alachlor are also presented. The authors address the difficulties of arriving at reliable scientific estimates of risk in such controversial areas, and the impact of this uncertainty on disagreements among different interest groups over how to manage those risks responsibly. In conclusion they attempt to delineate conditions under which consensus on the assessment and management of environmental health risks might be achieved among a wide range of interest groups. Risk and Responsibility will be of specific interest to policymakers and analysts, activists, and environmentalists, and of general interest to those working in relevant industries and members of the legal profession.